2002
DOI: 10.1002/jmr.565
|View full text |Cite
|
Sign up to set email alerts
|

A complete substitutional analysis of VIP for better tumor imaging properties

Abstract: Since numerous tumor cells overexpress the vasoactive intestinal peptide (VIP) receptor subtype 1 (VPAC(1)), VIP-dye conjugates would be useful as contrast agents for in vivo imaging. However, proteolytic degradation of VIP in vivo limits their diagnostic use and highlights the need for structurally optimized VIP derivatives with improved pharmacokinetics. Here, we applied parallel nano-synthesis of cleavable peptides on cellulose membranes to perform a complete VIP substitutional analysis. The resulting 504 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…It is therefore very tempting to suggest the use of growth-inhibiting VIP/PACAP analogs for the treatment of human tumors (16 -22). Moreover, a number of clinical and preclinical studies suggest that VIP/PACAP receptors may be promising molecular targets for tumor imaging and targeted radiotherapy (1,4,6,(23)(24)(25)(26). However, previous and present evidence indicates a highly abundant expression of VIP/PACAP receptors in normal human target tissues.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…It is therefore very tempting to suggest the use of growth-inhibiting VIP/PACAP analogs for the treatment of human tumors (16 -22). Moreover, a number of clinical and preclinical studies suggest that VIP/PACAP receptors may be promising molecular targets for tumor imaging and targeted radiotherapy (1,4,6,(23)(24)(25)(26). However, previous and present evidence indicates a highly abundant expression of VIP/PACAP receptors in normal human target tissues.…”
Section: Discussionmentioning
confidence: 75%
“…First, in vitro binding studies have shown that VIP/PACAP receptors are expressed in the great majority of most frequently occurring human tumors, including breast, ovarian, colon, insulinoma, carcinoid, pancreas, glioblastoma, meningioma, pituitary adenoma, and pheochromocytoma (16 -22). Second, VIP/PACAP receptor-positive intestinal and endocrine tumors can be visualized by in vivo VIP receptor scintigraphy (1,4,6,(23)(24)(25)(26). Third, application of VIP and PACAP analogs modulates tumor growth in animal models (2,3,(27)(28)(29)(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…[18,21,24] Two reports describe complete substitution analyses with preparation by SPOT technology that were applied in structure-function relationship investigations of a whole protein domain or a longer bioactive peptide. [25,26] Toepert et al [25] reported the synthesis and probing of a cellulose-membrane-bound peptide array containing 837 hYAP65 WW domain variants.…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy between potency and binding affinity for the VPAC 1 compared with native VIP is probably at least partially due to their greater metabolic stability, because each of these analogs has multialaninated substitutions similar to analogs 8 and 2 in the present study and analog 2 in a previous study (Igarashi et al, 2002a), each of which has enhanced metabolic stability. These results demonstrate that both the simplified VIP analogs 6 and 5 may have greater selectivity than the 65-fold selectivity of [Leu 22 ]VIP for hVPAC 1 over hVPAC 2 (Gourlet et al, 1998;Bhargava et al, 2002) and at least comparable and maybe greater than the widely used VPAC 1 -selective agonist (Gourlet et al, 1997a) [Lys 15 , Arg 16 , Leu 27 ]VIP(1-7)-GRF(8-27), which is reported to have a 53-to 169-fold selectivity for rVPAC 1 over rVPAC 2 transfected into Chinese hamster ovary cells in one study (Ito et al, 2000), but a 15,000-fold selectivity in another study (Gourlet et al, 1997a), and a 300-to 30,000-fold selectivity in hVPAC 1 /hVPAC 2 -containing cells (Gourlet et al, 1997a;Igarashi et al, 2002b).…”
Section: Discussionmentioning
confidence: 87%
“…However, [Ala 2,8,9,16,19,24,25 ]VIP (analog 8) had high affinity and potency for both VPAC subtypes and was much more metabolically stable than VIP in cells containing each VPAC subtype. These simplified, metabolically stable analogs should be useful for investigating the role of VPAC 1 in biological and pathological processes, for enhanced imaging of tumors overexpressing VIP receptors using VIP receptor scintigraphy (Virgolini, 1997;Thakur et al, 2000Thakur et al, , 2004Rao et al, 2001;Bhargava et al, 2002) as well as for possible VIP receptordirected antitumor treatment for tumors overexpressing VPACs (Gotthardt et al, 2004;Moody et al, 2004;Ou et al, 2005).…”
Section: Simplified Vip Agonists 379mentioning
confidence: 99%